2002
DOI: 10.1111/1467-8306.00295
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Applications of Interferometric Synthetic Aperture Radar (InSAR) in Geomorphology and Hydrology

Abstract: Interferometric synthetic aperture radar (InSAR) is a powerful geodetic tool used to construct digital elevation models of the earth's topography and to image centimeter-scale displacements associated with crustal deformation and the flow of ice sheets. The past decade has seen significant improvements in our understanding of earthquakes, volcanoes, and glaciers as a direct result of this technology. Geomorphology and hydrology can also benefit from InSAR. A small but growing body of work shows that it is poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 75 publications
0
66
0
Order By: Relevance
“…These images have a ground resolution of 30 m. They record the phase (time delay) and amplitude (energy intensity) of microwave echoes returned from Earth's surface. We select SAR intensity difference data because SAR amplitudes (energy intensities) are sensitive to roughness patterns of topographies (Smith 2002). This implies that any large-scale modifications in the surface roughness caused by e.g., gullying, dissecting, and landsliding are expected to yield a distinct pattern of intensity change that we intend to detect here.…”
Section: Introductionmentioning
confidence: 99%
“…These images have a ground resolution of 30 m. They record the phase (time delay) and amplitude (energy intensity) of microwave echoes returned from Earth's surface. We select SAR intensity difference data because SAR amplitudes (energy intensities) are sensitive to roughness patterns of topographies (Smith 2002). This implies that any large-scale modifications in the surface roughness caused by e.g., gullying, dissecting, and landsliding are expected to yield a distinct pattern of intensity change that we intend to detect here.…”
Section: Introductionmentioning
confidence: 99%
“…A review of emerging InSAR applications in hydrology and geomorphology found that some of the techniques were largely overlooked by the geographic and radar communities, and that the ability of InSAR to provide useful information to hydrologists and geomorphologists has been under-recognized (Smith 2002). Hydrogeologists have been relatively slow to use satellite remote sensing in their studies, attributed, in part, to the divide between the research community driving the instrument development and operation, and the hydrogeologic research community (Hoffmann 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There are different methodologies in differential interferometry (e.g., two-pass, three-pass, and four-pass interferometry) and with relatively new advanced algorithms (e.g., the Permanent Scatterers (PS) and the Small BAseline Subset (SBAS)) [9][10][11]. These techniques enable the mapping of subtle vertical surface movements (e.g., due to subsidence) down to millimeters [12][13][14][15][16][17].…”
Section: Sar Interferometrymentioning
confidence: 99%